Biological strategies for oligo/polysaccharide synthesis: biocatalyst and microbial cell factory. (15th April 2021) - Zhao, Liting; Ma, Zhongbao; Yin, Jian; Shi, Guiyang; Ding, Zhongyang
Highlights: Novel and improved glycoenzymes constructing the optimized routes can increase the production of sugar donor significantly. Construction and extension of scaffolds with enzymatic casscade reaction have facilitated the green manufacture of structurally defined oligo/polysaccharide. Cell factory allows the integrating and balancing of the pathway modules to enhance the metabolic flux towards oligo/polysaccharides. Abstract: Oligosaccharides and polysaccharides constitute the principal components of carbohydrates, which are important biomacromolecules that demonstrate considerable bioactivities. However, the variety and structural complexity of oligo/polysaccharides represent a major challenge for biological and structural explorations. To access structurally defined oligo/polysaccharides, biological strategies using glycoenzyme biocatalysts have shown remarkable synthetic potential attributed to their regioselectivity and stereoselectivity that allow mild, structurally controlled reaction without addition of protecting groups necessary in chemical strategies. This review summarizes recent biotechnological approaches of oligo/polysaccharide synthesis, which mainly includes in vitro enzymatic synthesis and cell factory synthesis. We have discussed the important factors involved in the production of nucleotide sugars. Furthermore, the strategies established in the cell factory and enzymatic syntheses are summarized, and we have highlighted concepts like metabolic flux rebuilding and regulation, enzyme engineering, and route design as important strategies. The research challenges and prospects are also outlined and discussed.